Polycyclic aromatic hydrocarbon (PAH) level in Bivalves and gastropods from petroleum-contaminated shorelines of TINMAR and tando four years after the M/T Solar I oil spill. - Guarino, Emyflor L.
Polycyclic aromatic hydrocarbons are considered as a major class of environmental hazardous organic compounds due to their persistence and known toxic and carcinogenic properties. Four years after the M/T Solar 1 oil spill, levels of polycyclic aromatic hydrocarbons (PAH) were determined in some bivalves and gastropods species from the petroleum-contaminated area within Taklong Island National Marine Reserve (TINMAR) and Tando. In this study, the summation19PAH detected from all the species collected ranged from 0.90to 15.40 ug/g wet weight. PAH composition was dominated by parent and low molecular weight PAHs. Individual PAH levels ranged from 0.01 to 15.40 ug/g wet weight with naphthalene accounting for the highest level. Computed benzo(a)pyrene equivalent (BaPE) values for some species suggest further monitoring for the protection of human health. The results in this study showed that four years after the oil spill some bivalves and gastropods collected were found to have detectable levels of PAH compounds (> 44 ppb BaPE) that can pose a risk to human health.